Extracellular matrix protein signature of recurrent spontaneous cervical artery dissection. (13th October 2020) - Mayer, Lukas; Pechlaner, Raimund; Barallobre-Barreiro, Javier; Boehme, Christian; Toell, Thomas; Lynch, Marc; Yin, Xiaoke; Willeit, Johann; Gizewski, Elke R.; Perco, Paul; Ratzinger, Gudrun; Kiechl, Stefan; et al.
Abstract : Objective: To assess whether connective tissue disorder is evident in patients with spontaneous cervical artery dissection and therefore identify patients at risk of recurrence using a cutting-edge quantitative proteomics approach. Methods: In the ReSect study, all patients with spontaneous cervical artery dissection treated at the Innsbruck University Hospital since 1996 were invited to attend a standardized clinical follow-up examination. Protein abundance in skin punch biopsies (n = 50) was evaluated by a cutting-edge quantitative proteomics approach (liquid chromatography–mass spectrometry) that has hitherto not been applied to such patients. Results: Patients with 1-time single-vessel (n = 19) or multiple-vessel (n = 13) dissections did not differ between each other or compared to healthy controls (n = 12) in protein composition. Patients with recurrent spontaneous cervical artery dissection (n = 6), however, showed significantly different expression of 25 proteins compared to the other groups combined. Literature review and Gene Ontology term annotation check revealed that 13 of the differently expressed proteins play a major role in the structural integrity of connective tissue or are linked to connective tissue disorders. These proteins showed clustering to a collagen/elastin cluster and one consisting of desmosome related proteins. Conclusion: This study unravels an extracellular matrix protein signature of recurrent spontaneous cervical artery dissection. In the long run and after large-scale validation, our findings may well assist in identifying patients at risk of recurrent spontaneous cervical artery dissection and thus guide therapy.